PENGARUH DISIPLIN KERJA, GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI KANTOR DINAS PERHUBUNGAN KABUPATEN KONAWE - Tauwi, Tauwi (Aksara Public, 2019)
This study aims to determine the effect of work discipline, leadership style, and motivation on the performance of employees of the Konawe District Office of Transportation. The population in this study were 38 people, and the sample in this study was taken as many as 38 respondents. This study uses multiple linear regression analysis using the F test and t-test with SPSS Version 16.0. Based on the results of the research conducted, it can be concluded that the leadership style has a positive and significant effect on employee performance at the Konawe District transportation office, the Work Environment has a positive and significant effect on the performance of Civil Servants at Konawe District Social Service Office, Organizational Climate has a positive and significant effect on performance Employee at Konawe District transportation office.